Identification of Good University Governance Principles in Society 5.0 - Santoso, Seno; Pramono, Suwito Eko; Handoyo, Eko; Yulianto, Arief (Universitas Negeri Semarang, 2024)
Good governance is a critical aspect of effective public administration, significantly impacting the quality of services provided to the community. This study aims to identify and implement good governance principles within rural local governments in the context of Society 5.0. Utilizing a qualitative research approach, the study seeks to uncover the specific principles and indicators of good governance as recognized in existing literature and contextualize them within the advanced societal framework of Society 5.0. The methodology involves thematic analysis of interviews and focus group discussions to determine the key governance principles and their practical applications. Data were collected from various rural local governments, and the findings highlight significant differences in governance perceptions and practices. The study reveals that transparency, accountability, public participation, responsiveness, and equity are the most critical factors for achieving good governance in rural areas. These principles, when properly implemented, enhance service delivery, reduce corruption, and improve community trust in local authorities. The results provide valuable insights for policymakers and administrators striving to strengthen governance in rural regions, offering a structured approach to adopt best practices and foster sustainable development in the era of Society 5.0.